2013
DOI: 10.4236/ajps.2013.410236
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Mungbean Yellow Mosaic Virus (MYMV) in Inter and Intra Specific Crosses of Mungbean (<i>Vigna radiata</i>)

Abstract: The objective of this research was to study the mode of inheritance of resistance to mungbean yellow mosaic virus (MYMV) in inter TNAU RED × VRM (Gg) 1 and intra KMG 189 × VBN (Gg) 2 specific crosses of mungbean. An infector row technique was used for evaluating parents, F 1 , F 2 and F 3 plants for MYMV resistance. No insecticide was sprayed in order to maintain the natural whitefly population in experimental field. In the field condition, only after 80% of plants showed MYMV incidence, and the scoring of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 3 publications
1
28
0
Order By: Relevance
“…This study confirmed the findings that the resistance against mungbean yellow mosaic virus is very scarce (Ahmad, 1975;Sahoo and Hota, 1991;Singh et al, 1996;Saleem et al, 1998;Bashir, 2005;Shad et al, 2006;Akhtar et al, 2011;Iqbal et al, 2011). This scarcity of resistant source is actually due to low proportion of recessive alleles (Sudha et al, 2013) in natural gene pool which also implies that recessive allele is mutated form of wild gene conferring susceptibility. Reported resistant genotype can be used as resistant source in breeding programs for the development of high yielding and mungbean yellow mosaic disease resistant varieties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study confirmed the findings that the resistance against mungbean yellow mosaic virus is very scarce (Ahmad, 1975;Sahoo and Hota, 1991;Singh et al, 1996;Saleem et al, 1998;Bashir, 2005;Shad et al, 2006;Akhtar et al, 2011;Iqbal et al, 2011). This scarcity of resistant source is actually due to low proportion of recessive alleles (Sudha et al, 2013) in natural gene pool which also implies that recessive allele is mutated form of wild gene conferring susceptibility. Reported resistant genotype can be used as resistant source in breeding programs for the development of high yielding and mungbean yellow mosaic disease resistant varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Mungbean is an important legume crop of Asia which produces almost 90% of the total global production (Sudha et al, 2013). It is a nutritive crop with high nutrient value which contains 20-24% protein and 60-65% carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique was applied for screening of mungbean progenies (F 2 ) derived from a cross between Vamban (Gg) 2 (susceptible) Â KMG 189 (MYMV resistant) (Karthikeyan et al, 2011). Later, a similar approach was used for screening of 78 mungbean germplasm lines for resistance to MYMV (Sudha et al, 2013).…”
Section: Yellow Mosaicmentioning
confidence: 99%